A framework to analyze the efficiency of private Tahfiz in Malaysia / Nor Tasik Misbahrudin and Abd Halim Mohd Noor - Misbahrudin, Nor Tasik; Mohd Noor, Abd Halim (Center for Islamic Philantrophy & Social Finance (CIPSF), 2022)
The increasing demand for Tahfiz has increased the number of Tahfiz institutions operating in Malaysia. Many Tahfiz institutions have been developed to fulfill the market demand. Unfortunately, this institution is reported to face several problems that can hinder its performance. Hence, measuring its efficiency is crucial because society needs to know the level of efficiency of the institutions that are responsible for student memorization and ensure the objectives can be achieved. Hence, Data Envelopment Analysis (DEA) is chosen as a measurement approach to measure the efficiency of the Tahfiz institution. Thus, this concept paper will highlight the importance of measuring performance and proposing a measurement approach to measure the performance of tahfiz institutions in Malaysia